"Kind of Natural, Kind of Wrong": Young People's Beliefs about the Morality, Legality, and Normalcy of Sexual Aggression in Public Drinking Settings. Issue 1 (4th November 2016) - Tinkler, Justine E.; Becker, Sarah; Clayton, Kristen A.
Abstract : Unwelcome touching, groping, and kissing are illegal, but widely tolerated in public drinking settings. This contingency in the law's response means that patrons routinely negotiate the moral boundaries of nonconsensual sexual contact. We use 197 interviews with college‐age individuals to examine the discursive strategies young people employ when negotiating those boundaries. We find that most interviewees have experiences with sexual aggression, do not categorize it as aggression, but advocate for stronger legal punishments against offenders. In accounting for this paradox, they draw on contradictory legal and cultural narratives that both normalize and condemn men's sexual aggression. We build on legal consciousness theories and gender theories by highlighting the complex ways that gender stereotypes enshrined in law are implicated in the construction of a social problem. We also contribute to the sociology of culture by explicating the often unconscious link between culture and action revealed in young people's narratives about sexual aggression.